WHO IS AFRAID OF FEMINISM? MISRECOGNITION AND THE POLITICS OF ACTIVE IGNORANCE - Volta, Eleonora (Soft Power, 2025)
Una giustizia a due dimensioni. Redistribuzione e riconoscimento nell’opera di Nancy Fraser includes an introduction and seven chapters written by Anna Cavaliere. In all, this is an excellent work that plumbs the dimensions of redistribution, recognition, and political representation in Nancy Fraser’s theory of justice in light of the changes that have occurred with the rise of neoliberal globalisation. In this note on Cavaliere’s book, I will focus my comments on selected chapters to address two interrelated issues. In the first section, I build on Nikolas Kompridis’s critique of Fraser’s standard of publicity to highlight the role of active ignorance in defining what merits the title of injustice. In the second section, I take my cue from Fraser’s critique of second-wave feminism to shed light on the conceptual hostility that actively distorts feminist claims and weakens their transformative power.